(Table 2, page 1182) Partial composition of manganese encrustations from Gulf of Aden - Glasby, Geoffrey P; Tooms, J S; Cann, Joe R (Supplement to: Glasby, GP et al. (1971): The geochemistry of manganese encrustations from the Gulf of Aden. Deep Sea Research and Oceanographic Abstracts, 18(12), 1179-1187, https://doi.org/10.1016/0011-7471(71)90025-8, 1971)
Manganese encrustations from two adjacent sampling sites in the Gulf of Aden display markedly different compositional characteristics. The enrichment of manganese, and consequent depletion of iron and a series of trace elements, in the manganiferous crusts from Sta. 6243 is attributed to the diagenetic remobilisation of manganese within the sediment column and the resultant enrichment of this element in the encrustations from this station. Molybdenum, and possibly nickel, appear to show similar migration characteristics. Submarine vulcanism does not appear to play any significant role in controlling nodule composition within the area.